Wearable Activity Monitor Use Is Associated With the Aerobic Physical Activity Guidelines and Walking Among Older Adults. Issue 5 (June 2021) - Zytnick, Deena; Kumar, Gayathri S.; Folta, Sara C.; Reid, Kieran F.; Tybor, David; Chomitz, Virginia R.
Purpose: To examine wearable activity monitor (WAM) use and its association with meeting the 2008 aerobic Physical Activity Guidelines (PAG) and walking among older adults. Design: Cross-sectional. Setting: FallStyles 2015 national consumer panel survey. Sample: 1, 317 U.S. adults aged ≥ 60 years. Measures: Self-reported WAM use, meeting aerobic PAG, and walking. Covariates included age, sex, race/ethnicity, education level, marital status, annual household income, and geographic region of the country. Analysis: Chi-square tests to examine associations between WAM use and respondent demographic characteristics. Logistic regressions to explore associations between WAM use and meeting aerobic PAG and walking adjusted for demographics (e.g., education, income). Results: Among older adults, 8.0% were current WAM users and 11.3% were past WAM users. Current WAM use was most prevalent among those aged 65-74 (16.6%), females (9.4%), college graduates (13.8%), and those with incomes 75, 000-99, 999 (14.8%). Current WAM users were more likely than never WAM users to report meeting aerobic PAG (OR: 3.98; 95% CI: 2.07, 7.66) and walking (OR: 3.90; 95% CI: 1.57, 9.69). Past and never WAM use were not associated with meeting aerobic PAG or walking. Conclusion: We found current WAM use is associated with meeting the aerobic PAG and walking among older adults. Further longitudinal research is needed to understand whether WAM could promote increased PA among older adults.